Factores que inciden en la violencia e inseguridad contra las mujeres en el sector de la Av. 24 de mayo de la ciudad de Quito, experiencias de las redes locales de atención y prevención. - Cáceres Gallardo, Lidia Guadalupe (2015)
Around the world violence against women is rooted in many different ways of discrimination, inequality and oppression interrelated and deeply linked to patriarchal power. This is a persistent problem and unacceptable phenomenon. Violence against women is a consistent pattern of explotation, domination and power. Gender discrimination is the cause of violence against women, social norms and gender stereotypes come to perpetuate this phenomenon. Because of the impact that violence has on women, all the efforts are focus principally on responses and services for survivors, but the best way to avoid gender violence is trying to prevent its origins and root causes. This paper explain various factors that has influence in violence and insecurity against women and their experiences of prevention and protection of local networks is performed, taking into account the socioeconomic reality, politics, public participation and fulfillment of rights. Additionally, the problem of gender violence against women is studied because we are looking for an effective solution to this phenomenon. The impacts of violence reverberate through a different dimension, affecting the full exercise of their citizenship, socialization, solidarity and civic responsibility in general. Local authorities involved limitedly in the field of public safety, sectional organizations begin to design policies aimed at strengthening citizen participation on security. Besides that the government does not give an integral vision but a segmented is stablish, a real comprehensiveness will be at the same time that the crime faces , the citizenship keep building and implementing ways in order to prevent conflicts and violence will decline in these measures. To achieve this goal it is necessary that the central government and regional governments assigned enough resources to train justice instances involved in this issues, as well as the citizenship who must be aware of their important role in order to participate in the achievement of a life full of respect, equality and without discrimination.